2019
DOI: 10.1039/c8ce02122h
|View full text |Cite
|
Sign up to set email alerts
|

Two triphenylamine-based luminescent metal–organic frameworks as a dual-functional sensor for the detection of nitroaromatic compounds and ofloxacin antibiotic

Abstract: Two solvent-induced luminescent MOFs have been synthesized and MOF1 can be employed as a dual-functional fluorescence sensor for nitroaromatics and antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Figure b shows the linear relationship of the values of I 0 / I – 1 and the NFT concentrations in the full detection concentration range. The calculated K sv value of NFT is as high as 4.64 × 10 4 M –1 , and the corresponding R 2 value is obtained as 0.9981, which shows that MOF 1 is the most sensitive sensor material. The selectivity of MOF 1 is a very significant factor for sensors in real applications, which can be studied and proven by the selective trials. It is found that all emission spectra almost disappeared only after adding NFT in the detected system (Figure c), proving that MOF 1 has excellent selectivity toward NFT even in other disturbed antibiotics.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Figure b shows the linear relationship of the values of I 0 / I – 1 and the NFT concentrations in the full detection concentration range. The calculated K sv value of NFT is as high as 4.64 × 10 4 M –1 , and the corresponding R 2 value is obtained as 0.9981, which shows that MOF 1 is the most sensitive sensor material. The selectivity of MOF 1 is a very significant factor for sensors in real applications, which can be studied and proven by the selective trials. It is found that all emission spectra almost disappeared only after adding NFT in the detected system (Figure c), proving that MOF 1 has excellent selectivity toward NFT even in other disturbed antibiotics.…”
Section: Resultsmentioning
confidence: 87%
“…It clearly found that the luminescence behavior of MOF 1 is similar to that of this linker, but a slight blue-shift phenomenon was mainly attributed to the metal-coordination interaction to enhance the ligand rigidity and decrease the energy loss by radiationless decay. Antibiotics are easily dissolved in water, so water was selected as the detectable system. From the previous reports, some MOFs have been implemented as luminescent sensors to monitor antibiotics. In addition, MOF 1 can preserve the luminescent behavior in water after 1 day (Figure b). This encouraged us to explore the detectability of MOF 1 to antibiotics in aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation and exploration of the luminescence quenching mechanism are significantly important work to gain deep insight into the relationship of the structure and detectability. Taking into account the previous reports, most of the possible quenching mechanisms are summarized and divided into four categories: guest adsorption, host–guest interaction, skeleton damage, and light energy competition. First, the maximum emission peak of MOF 1 in NFT or NFZ (0.06 mM) was collected at different immersion times to investigate the signal response rates in Figure a. The luminescence intensity of ground 1 will sharply decrease to a minimum value after 75 s and retain this status for a long time.…”
Section: Resultsmentioning
confidence: 99%
“…When the LUMO level of the detected substance is lower, electrons are easily transferred to the detected substance, which results in the interference of energy transfer between the ligand and metal ions, leading to fluorescence quenching. 34,35 As shown in Fig. 10b, according to the DFT calculation, the LUMO levels of H 2 ox (−1.97 eV) and H 2 bct (−1.05 eV) was higher than that of chlorogenic acid (−2.13 eV).…”
Section: Mechanism Of Sensingmentioning
confidence: 89%